Effects of crochet technique associated with kinesiotherapy in patients with chronic low back pain - Alonso, Angélica Castilho; Nunes, Michele Figueira; Alves, Flávia Domingues; Souza, Michele Oio Rodrigues de; Prota, Cristina; Silva, Alexandre Sabbag da; Rica, Roberta Luksevicius; Maia, Adriano Fortes; Barbosa, Welmo Alcântara; Souza, Alana de Sena; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: The chronic low back pain (LBP) had been considered an important occupational disorder with several strategy available to treatment, however, few studies had been evaluated the treatment combination. Objectives: The aim of present study was compared the effects of combination of crocheting associated to Kinesiotherapy treatment and Kinesiotherapy isolated treatment on function of lumbar spine and pain during achievement of daily life in patients with chronic LBP. Methods: Forty subjects were distributed randomly in two groups: Crochetagem + Kinesioterapy (C; n: 18; 47.5 ± 7.75 years) and Kinesiotherapy (K, n: 18; 45.3 ± 8.93 years). The C group was treated by crocheting technique associated with kinesiotherapy using therapeutic ball. The K group performed a kinesiotherapy treatment using just a therapeutic ball. The following parameters were evaluated: abdominal strength, articular range motion and the data of Rolland Morris and Oswestry Disability Index questionnaires were evaluated before and after 8 weeks of treatment. Both groups performed all therapeutic sessions for 50 minutes, three times a week. Results: Significant differences (p<0.05) were found just on time to trunk flexion and extension, right and left lateral trunk, pain and abdominal strength. However, significant differences on time (p<0.05) was found on Rolland Morris and Oswestry data questionaries parameters just on C group, additionally the values of C group were lower than K group after treatment. Conclusion: Both kinesiotherapy isolated and association of crocheting and kinesiotherapy were useful to improve functional parameters, however the data from Rolland Morris and Oswestry questionaries were lower just on crocheting associated to kinesiotherapy group indicating increment on function of lumbar spine and decrease on pain during achievement of daily life.